2009
DOI: 10.1111/j.1582-4934.2009.00760.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genetic SSTR4 ablation on inflammatory peptide and receptor expression in the non‐inflamed and inflamed murine intestine

Abstract: The recently suggested pivotal role of somatostatin (SOM) receptor 4 (SSTR4) in inflammation and nociception in several non-intestinal organs and in gastrointestinal (GI) physiology, necessitates exploration of the role of SSTR4 in GI pathophysiology. Therefore, the role of SSTR4 in GI activity was explored by investigating the effects of SSTR4 deficiency on intestinal motility, smooth muscle contractility and on the expression of SSTRs and neuropeptides in the healthy and Schistosoma mansoni-infected murine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Previous studies have shown that amongst all SSTRs, SSTR4 is the only subtype that mediates analgesic effects of SST. Neurogenic and non-neurogenic inflammatory processes were significantly reduced upon administration of SSTR4 specific agonist in animal models [22]. Recently, SSTR specific knockout ( ko ) models have provided new insights for the role of SSTRs in certain pathophysiological conditions such as inflammation and analgesia [22], [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that amongst all SSTRs, SSTR4 is the only subtype that mediates analgesic effects of SST. Neurogenic and non-neurogenic inflammatory processes were significantly reduced upon administration of SSTR4 specific agonist in animal models [22]. Recently, SSTR specific knockout ( ko ) models have provided new insights for the role of SSTRs in certain pathophysiological conditions such as inflammation and analgesia [22], [23].…”
Section: Introductionmentioning
confidence: 99%
“…Neurogenic and non-neurogenic inflammatory processes were significantly reduced upon administration of SSTR4 specific agonist in animal models [22]. Recently, SSTR specific knockout ( ko ) models have provided new insights for the role of SSTRs in certain pathophysiological conditions such as inflammation and analgesia [22], [23]. Helyes et al, have described that SSTR4 ko mice are more susceptible to inflammation and exhibit sustained pain than wt mice [23].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the selective sst 4 agonist administered peripherally under similar conditions than the sst 1 agonist did not influence the VMR to repeated noxious CRD. In the somatic field, there is growing evidence that the sst 1,4 somatostatin agonist, TT-232 [17,51] and the sst 4 agonist, J-2156 [18], exert peripheral anti-inflammatory and analgesic effects in various acute and chronic inflammatory rodent models including chronic arthritis, or mono- and polyneuropathy conditions [45,56,57,61]. Further studies using different models of visceral pain, such as chemically-induced colonic inflammation or post-infectious hyperalgesia [32] will be required to elucidate the exact role of the sst 4 in visceral nociception linked with past or present gut inflammatory components.…”
Section: Discussionmentioning
confidence: 99%
“…These effects are mediated through ORs that comprise three subtypes-µ, δ, and κ, that are structurally related to SSTRs and share ~40% sequence homology. Recent studies have demonstrated that SSTRs also play a critical role in mediating analgesic effects of SST [188,221,222]. For instance, upon direct administration to the central and peripheral nervous system in animal model of post-operative and neoplastic pain, the SST analogue octreotide is both analgesic and morphine-sparing [223,224].…”
Section: Implication Of Somatostatin Receptors Heterodimerization mentioning
confidence: 99%